PENERAPAN OJS DALAM MOBILE/ANDROID YANG DIPERUNTUKKAN BAGI PEMBACA DAN AUTHOR - Sudaryanto Sudaryanto; Mohamad Ikhwandi (Institut Teknologi Dirgantara Adisutjipto, 2017)
One way to take advantage of current technological developments is to utilize the smartphone as a means of accessing the Internet network. Open Journal System Application (OJS) Application Design Concept (OJS) In Mobile / Android Covered For Readers and Author (OJS based on android) is where the application system will access the existing OJS database on the server then the data will be transferred into the application , So that OJS data on the server can be retrieved and can be entered into OJS Based Application android. Thus users / readers no longer need to access the browser, because in the Android-based OJS application will display the pdf-shaped article files.From the analysis of comparative function and viewing of OJS application that opened with browser, with OJS android based application, in essence has the same function that is displaying the work of ilmia from an institution from a researcher, but there are some deficiencies in OJS Application Based Android , Such as in the application can not display data that resides in OJS database as a whole.